2008
DOI: 10.2478/v10032-008-0025-0
|View full text |Cite
|
Sign up to set email alerts
|

Trichoderma spp. - The Cause of Green Mold on Polish Mushroom Farms

Abstract: Trichodermaspp. - The Cause of Green Mold on Polish Mushroom FarmsThe first reports concerning green mold on Polish mushroom farms are from 2002. In Europe and the United StatesTrichoderma harzianumwas initially described as a causative agent of the disease. However, soon two biotypes ofTrichoderma, Th2 in Europe and Th4 in America, were recognised as responsible for commercial losses and were designated as a new species namedT. aggressivum.Until now it has not been clear which species ofTrichodermaand which f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 11 publications
1
15
0
1
Order By: Relevance
“…Williams et al (2003) indicated that both above-mentioned biotypes were more aggressive in comparison with other isolates of T. harzianum. The first reports about the appearance of green mould in mushroom cultivations in Poland date back to 2002 (Szczech et al 2008). The authors of this study showed that the most frequently isolated species of the Trichoderma genus identified in mushroom producing farms included: T. harzianum, T. atroviride, T. aggressivum and T. longibrachiatum.…”
Section: Introductionmentioning
confidence: 90%
“…Williams et al (2003) indicated that both above-mentioned biotypes were more aggressive in comparison with other isolates of T. harzianum. The first reports about the appearance of green mould in mushroom cultivations in Poland date back to 2002 (Szczech et al 2008). The authors of this study showed that the most frequently isolated species of the Trichoderma genus identified in mushroom producing farms included: T. harzianum, T. atroviride, T. aggressivum and T. longibrachiatum.…”
Section: Introductionmentioning
confidence: 90%
“…[3,[5][6][7][8][9][10] During the past decade, the pathogen has dispersed into Central and South East Europe, Central America and Australia. [2,[11][12][13][14][15] Green mould caused by Trichoderma spp. is characterized by white mycelia of fastgrowing colonies on casing or substrate that change color to green after profuse sporulation.…”
Section: Introductionmentioning
confidence: 99%
“…In the early 1990s, green mould appeared in mushroom crops in North America, the USA and Canada, also causing enormous damage to mushroom production (Rinker, ; Romaine et al ., ). During the past decade, green mould disease of A. bisporus spread to Hungary (Hatvani et al ., ), Poland (Szczech et al ., ), Mexico (Romero‐Arenas et al ., ), Australia (Clift & Shamshad, ) and Croatia (Hatvani et al ., ). Trichoderma mycoparasitic species from the British Isles and North America were initially classified as Trichoderma harzianum Rifai (Samuels et al ., ).…”
Section: Introductionmentioning
confidence: 99%